Optimised protocol for the extraction of fish DNA from freshwater sediments. (5th July 2022) - Thomson‐Laing, Georgia; Howarth, Jamie D.; Vandergoes, Marcus J.; Wood, Susanna A.
Abstract: Monitoring fish is necessary for understanding population dynamics, tracking distribution patterns and evaluating conservation efforts. Molecular techniques targeting environmental DNA (eDNA) are now considered effective methods for detecting specific species or characterising fish communities. The analysis of DNA from lake‐surface sediments (sedDNA) can provide a time‐integrated sampling approach which reduces the variability sometimes observed in water samples. However, studies of sedDNA have had varying success in detecting fish. The present study aimed to determine the most effective extraction method for recovering fish DNA from lake‐surface sediments. A literature review was undertaken to identify DNA extraction methods used previously on aquatic sediments targeting aquatic and terrestrial animals. Five methods with various modifications were tested to establish their ability to desorb extracellular DNA. Based on these results, two methods were selected and optimised, and the recovery of fish sedDNA characterised using droplet digital PCR assays targeting eel and perch ( Anguilla australis, Anguilla dieffenbachii, Perca fluviatilis ). A range of sediment masses (0.25–20 g) were assessed to establish the optimal amount required to accurately assess fish sedDNA. The DNA extraction methods found to be most effective at recovering extracellular DNA spiked into small sediment masses (0.25 g) were the DNeasy PowerSoil DNA Isolation Kit (QIAGEN), and the ABPS protocol which involved an initial alkaline buffer extraction followed by the PowerSoil extraction kit. For larger sediment masses (>0.25 g) the ABPS protocol or the DNeasy PowerMax Soil Kit (QIAGEN) with an additional ethanol DNA concentration step (PMET protocol) yielded the highest concentrations of target genes across a range of lake sediments. Larger sediment masses (≤20 g was tested) increased the likelihood of detection of fish in sedDNA. Optimisation of the ABPS protocol was required (65°C incubation temperature, pooling of multiple PowerSoil extractions) to overcome technical challenges related to co‐precipitation of organic content in lake‐surface sediments. This optimised ABPS protocol was called the "Lakes ABPS protocol". We recommend the use of the Lakes ABPS protocol as it is cheaper than the PMET protocol. Additionally, after the first extraction step, the process can be automated on a DNA extraction robot, allowing for higher sample throughput. A mass of 10 g is suggested, although higher detection is achieved with more sediment, a suite of challenges, such as co‐precipitation of organic content, are encountered when the amount is increased. This study highlights the complexity of the extraction and detection of fish sedDNA from lake sediment, especially when it has a high organic content. We have optimised a DNA extraction method to overcome some of these complexities that can be applied to a wide range of lake sediments.